Analysis of the Relationship between Self-Management Behavior and Blood Pressure Control in Adult Hypertension Patients in Faith-Based Communities - Sergio Yudi Midu; Eva Chris Veronica Gultom; Jon Parulian Simarmata; Ballsy Cicilia Albertina Pangkey; Bima Adi Saputra (Jurnal Keperawatan Profesional, 2026)
Hypertension is a medical condition that significantly increases the risk of other diseases and can cause fatal complications such as heart attack, stroke, kidney failure, and even death. Objective: To determine the relationship between self-management behavior and blood pressure in patients with hypertension. Methods: This study used a quantitative descriptive design with a cross-sectional research design. The population in this study was the Tambakrejo GKJW congregation. Sampling was conducted using non-probability sampling with purposive sampling. The sample in this study consisted of 93 members of the Tambakrejo GKJW congregation who suffered from hypertension. Data collection was conducted using the HSMBQ questionnaire and a digital sphygmomanometer. Data analysis was conducted using the chi-square test.  Results: The majority of respondents were middle-aged adults (41–60 years) (58.1%) and female (63.4%). Most respondents had suffered from the disease for more than 5 years (55.9%). Based on blood pressure, most respondents had controlled hypertension (53.8%). In addition, most respondents had poor self-management behavior (61.3%). Statistical tests showed a significant relationship between self-management behavior and the blood pressure status of respondents (p = 0.007), where respondents with good self-management tended to have more controlled blood pressure than respondents with poor self-management.  Implications: Strengthening self-management behavior through collaboration between health workers and religious communities has the potential to improve blood pressure control in people with hypertension.